An Exploratory Study on Human Factor Analysis of Medical Accidents Using the SHELL (Software, Hardware, Environment, Liveware) Model - Su-Jeong Lee (Hanggong uju uihakoeji, 2023)
The SHELL (Software, Hardware, Environment, Liveware) model is one of the models for determining the cause of aviation accidents. The human factors of medical accidents are analyzed through the SHELL model. This study is a case study that analyzed a total of three cases, including two medical accident court precedents and one large fire at a medical institution. In the human factor analysis of cases 1 and 2, the main factors were that liveware (human) violated the duty of care and did not follow the guidelines of the institution. The large fire incident in the hospital in Case 3 was caused by a lack of awareness of the safety of managers, the installation of illegal facilities and environments, lack of medical staff’s response and training, and the condition of patients who were mostly elderly. The liveware at the center of the SHELL model is the most important human factor, and the environment, facilities, and equipment surrounding liveware must be supplemented to prevent future medical accidents.